Impact Analysis of Integrated Waste Management Program on Reducing Sedimentation of Saguling Reservoir by PT. PLN Indonesia Power UBP Saguling - Rosyidah, Ummi; Sofiyah; Raihan, Dhimas; Kurniawan, Taufan (International Journal of Science and Society, 2024)
Saguling Reservoir, located in West Bandung Regency, West Java Province, is one of the assets for energy sources for hydroelectric power generators (PLTA). The sustainability of the reservoir is one of the important aspects that needs to be considered to maintain its role and benefits. Sedimentation is a crucial issue in determining the sustainability of a reservoir. Increased waste production in the Bandung Raya area is one of the contributing materials to sedimentation if left uncontrolled. PT. PLN Indonesia Power UBP Saguling initiated an integrated waste management program, addressing waste from upstream areas to those that flow into the Saguling reservoir, as part of their efforts in supporting reservoir conservation. This study aims to determine the impact of implementing an integrated waste management, a community empowerment program, on reducing sedimentation. The secondary data analysis was utilized in the current research. The decrease in reservoir sedimentation was analyzed using data on the amount of waste absorption managed by community groups fostered by PT. PLN Indonesia Power UBP Saguling. The integrated waste management program reviewed from 2020 to 2024 was able to reduce sedimentation by 5,843 m3 with a percentage of sedimentation reduction of 0.36%.